Evaluating 21st century key human resource management challenges in Nigeria / Matthew Funsho Bello and Kajo Aondohemba Emmanuel - Bello, Matthew Funsho; Emmanuel, Kajo Aondohemba (Universiti Teknologi MARA, 2021)
It is no longer news that the human resource is the most significant and important resource of any organization and any effort made in motivating the workforce will pay off significantly. In this era of globalization and the 21st century, organizations that are failing to adequately identify, monitor and develop HRM policies that will lead to efficient goal achievement, are bound to experience series of inefficiencies and loses therefore leading to poor performance in terms of low profitability and poor growth. There is a wide gap between the manager of human resource and the human resource themselves. This study adopted robust conceptual and empirical review literatures on the subject. The paper there examines challenges posed by individuals, governments and unions on human resource management in Nigeria such as an unavailability of Executive Information System (EIS), the wide gap existing between the management and staff, introduction of flexitime, no external interference or pressures in the recruitment and promotion of staff, workplace diversity, changing mix of workforce, values, demands of employers and governments are evident. The Niger Delta militancy, kidnapping, gender discrimination, nepotism and ethnic sentiments are evident and are also factors affecting HRM in Nigeria in this 21st Century. It is concluded that the design of programmes for recruitment, training and development, integration, maintenance and separation of the employee cannot be possible without the acceptance of the organizational members. A team building and policy formulation on solving the workplace diversity is fundamental to achieving the set organizational goals.